Clinical application of MOSkin dosimeters to rectal wall in vivo dosimetry in gynecological HDR brachytherapy. (September 2017) - Carrara, M.; Romanyukha, A.; Tenconi, C.; Mazzeo, D.; Cerrotta, A.; Borroni, M.; Cutajar, D.; Petasecca, M.; Lerch, M.; Bucci, J.; Richetti, A.; Presilla, S.; et al.
Highlights: 3 MO Skins were assembled over a common rectal probe to perform in vivo dosimetry. Mean discrepancy between measured and calculated doses was 2.2 ± 6.9%. 89.2% of the measurements resulted in dose discrepancies within ±10%. Discrepancy between planned and measured doses increases with planning time. Abstract: Purpose: Three MO Skin s dosimeters were assembled over a rectal probe and used to perform in vivo dosimetry during HDR brachytherapy treatments of vaginal cancer. The purpose of this study was to verify the applicability of the developed tool to evaluate discrepancies between planned and measured doses to the rectal wall. Materials and methods: MO Skin dosimeters from the Centre for Medical Radiation Physics are particularly suitable for brachytherapy procedures for their ability to be easily incorporated into treatment instrumentation. In this study, 26 treatment sessions of HDR vaginal brachytherapy were monitored using three MO Skin mounted on a rectal probe. A total of 78 measurements were collected and compared to doses determined by the treatment planning system. Results: Mean dose discrepancy was determined as 2.2 ± 6.9%, with 44.6% of the measurements within ±5%, 89.2% within ±10% and 10.8% higher than ±10%. When dose discrepancies were grouped according to the time elapsed between imaging and treatment (i.e., group 1: ≤90 min; group 2: >90 min), mean discrepancies resulted in 4.7 ± 3.6% and 7.1 ± 5.0% for groups 1 and 2, respectively. Furthermore, the position of the dosimeter on the rectal catheter was found to affect uncertainty, where highest uncertainties were observed for the dosimeter furthest inside the rectum. Conclusions: This study has verified MO Skin applicability to in-patient dose monitoring in gynecological brachytherapy procedures, demonstrating the dosimetric rectal probe setup as an accurate and convenient IVD instrument for rectal wall dose verification. Furthermore, the study demonstrates that the delivered dose discrepancy may be affected by the duration of treatment planning.